Singlet and triplet energy transfer dynamics in self-assembled axial porphyrin–anthracene complexes: towards supra-molecular structures for photon upconversion. Issue 11 (1st March 2018) - Gray, Victor; Küçüköz, Betül; Edhborg, Fredrik; Abrahamsson, Maria; Moth-Poulsen, Kasper; Albinsson, Bo
Abstract : Singlet and triplet energy transfer dynamics in anthracene–ruthenium porphyrin complexes, and their application to photon upconversion. Abstract : Energy and electron transfer reactions are central to many different processes and research fields, from photosynthesis and solar energy harvesting to biological and medical applications. Herein we report a comprehensive study of the singlet and triplet energy transfer dynamics in porphyrin–anthracene coordination complexes. Seven newly synthesized pyridine functionalized anthracene ligands, five with various bridge lengths and two dendrimer structures containing three and seven anthracene units, were prepared. We found that triplet energy transfer from ruthenium octaethylporphyrin to an axially coordinated anthracene is possible, and is in some cases followed by back triplet energy transfer to the porphyrin. The triplet energy transfer follows an exponential distance dependence with an attenuation factor, β, of 0.64 Å −1 . Further, singlet energy transfer from anthracene to the ruthenium porphyrin appears to follow a R 6 Förster distance dependence. Porphyrin–anthracene complexes are also used as triplet sensitizers for triplet–triplet annihilation (TTA) based photon upconversion, demonstrating their potential for photophysical and photochemical applications. The triplet lifetime of the complex is extended by the anthracene ligands, resulting in a threefold increase in the upconversion efficiency, Φ UC to 4.5%, compared to the corresponding ruthenium porphyrin–pyridine complex. Based on the results herein we discuss the future design of supra-molecular structures for TTA upconversion.